Optimizing Public Information Dispute Resolution Through Digital Business Process Reengineering Strategies - Muhammad Rafid Mursyaday Putra Satria; Ilyas Nuryasin (bit-Tech, 2025)
This study applies Business Process Reengineering (BPR) combined with digital document management to improve the efficiency of public information dispute resolution at the Ministry of Religious Affairs in Batu City, Indonesia. It identifies key inefficiencies in manual workflows, such as document sorting, verification, and archiving, which slow service delivery and reduce accuracy. By redesigning processes to eliminate non-value-adding steps and integrating automation via a web-based dashboard for real-time monitoring, the study achieves significant operational improvements. Using ASME-standard process mapping and throughput efficiency testing—a rigorous quantitative approach rarely employed in public sector BPR evaluations—the research measures process performance objectively. Results show throughput efficiency increased from 37.32% to 69.43%, with substantial reductions in processing time, enhanced document accessibility, and strengthened information security. Automated workflows reduce human error and improve traceability in dispute handling. The novelty of this study lies in its methodological integration of engineering standards with public administration reform and its practical application of digital BPR in a complex, bureaucratic Indonesian government context. This provides robust empirical evidence on how digital transformation synergized with BPR can enhance transparency, responsiveness, and service quality in public dispute management. The findings offer valuable insights for governmental institutions aiming to modernize administrative procedures, improve accountability, and align operational performance with citizen expectations in the digital era.